Implementation of differentiated learning in supporting Merdeka Belajar to improve senior high school student’s learning outcomes - Rezky Nefianthi; Rabiatul Adawiyah; Fujianor Maulana (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Differentiated learning has advantages, which include being able to improve student learning outcomes, optimize student needs, and increase student enthusiasm for learning. Besides that, students, when learning the concept of food digestion, appear passive and unenthusiastic, and this results in low learning outcomes. The research aim is to determine the improvement in learning outcomes of class XI students in the biology subject, the concept of food digestion. This research was the Classroom Action Research (CAR) method, which consists of planning, implementation, observation and reflection. The subjects of this class action research were XI class students at Anjir Pasar State Senior High School, a total of 28 students, consisting of 17 females and 11 males. This research was divided into two cycles. Based on this research finding, differentiated learning is able to improve the achievement of student learning outcomes. The average learning outcomes of cycle I meeting 1 with a score of 75 and meeting 2 with a score of 79.85. In cycle II, meeting 3, student learning outcomes increased with an average score of 81.25 and in meeting 4, with a score of 82.32. Differentiated learning increases enthusiasm, is able to train independence, improves learning outcomes in each cycle, and obtains positive responses from students. This research needs to be tested for its long-term impact through ongoing research, and teachers can also be given training to support the implementation of this learning method.Abstrak Pembelajaran berdiferensiasi memiliki keunggulan yang meliputi dapat meningkatkan hasil belajar siswa, mengoptimalkan kebutuhan siswa, dan meningkatkan antusiasme siswa dalam belajar. Disamping itu, siswa dalam pembelajaran konsep pencernaan makanan tampak pasif, tidak antusias, dan berdampak pada rendahnya hasil belajar. Tujuan penelitian ini adalah untuk mengetahui peningkatan hasil belajar siswa kelas XI pada mata pelajaran biologi konsep pencernaan makanan. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang terdiri dari perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian tindakan kelas ini adalah siswa kelas XI SMA Negeri Anjir Pasar yang berjumlah 28, terdiri dari 17 perempuan dan 11 laki-laki. Penelitian ini terbagi menjadi 2 siklus. Berdasarkan temuan penelitian ini, pembelajaran berdiferensiasi mampu meningkatkan pencapaian hasil belajar siswa. Rata-rata hasil belajar siklus I pertemuan 1 dengan skor 75 dan pertemuan 2 dengan skor 79,85. Pada siklus II pertemuan 3 hasil belajar siswa meningkat dengan skor rata-rata 81,25 dan pertemuan 4 dengan skor 82,32. Pembelajaran berdiferensiasi meningkatkan antusiasme, mampu melatih kemandirian, meningkatkan hasil belajar pada setiap siklus, dan memperoleh respon positif dari siswa. Penelitian ini perlu diuji dampak jangka panjangnya melalui penelitian berkelanjutan dan guru juga dapat diberikan pelatihan untuk mendukung implementasi metode pembelajaran ini.